2017
DOI: 10.1002/cne.24152
|View full text |Cite
|
Sign up to set email alerts
|

Spatial patterning of excitatory and inhibitory neuropil territories during spinal circuit development

Abstract: To generate rhythmic motor behaviors, both single neurons and neural circuits require a balance between excitatory inputs that trigger action potentials and inhibitory inputs that promote a stable resting potential (E/I balance). Previous studies have focused on individual neurons and have shown that, over a short spatial scale, excitatory and inhibitory (E/I) synapses tend to form structured territories with inhibitory inputs enriched on cell bodies and proximal dendrites and excitatory inputs on distal dendr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…We recently showed that zebrafish gabra1 -/- and depdc5 -/- epileptic mutants displayed markedly fewer inhibitory synapses compared to age-matched control larvae, showing that these two mutants display brain development defects [21,22]. To determine whether Scn1Lab deficiency also induced unbalanced excitatory/inhibitory post-synaptic outputs, we analyzed and compared, by immunocytochemistry, the distribution of the two post-synaptic populations on brain sections of 5 dpf control and Scn1Lab-depleted larvae, using anti-PSD-95 and anti-gephyrin antibodies, which label excitatory and inhibitory post-synaptic terminals, respectively [23]. Quantification of the two post-synaptic populations showed a marked increase in PSD-95 labeling (Figure 2B,C; p < 0.01) combined with a clear decrease of that of gephyrin (Figure 1E,F; p < 0.01), in scn1Lab AUG morphants, compared to controls (Figure 2A,D).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that zebrafish gabra1 -/- and depdc5 -/- epileptic mutants displayed markedly fewer inhibitory synapses compared to age-matched control larvae, showing that these two mutants display brain development defects [21,22]. To determine whether Scn1Lab deficiency also induced unbalanced excitatory/inhibitory post-synaptic outputs, we analyzed and compared, by immunocytochemistry, the distribution of the two post-synaptic populations on brain sections of 5 dpf control and Scn1Lab-depleted larvae, using anti-PSD-95 and anti-gephyrin antibodies, which label excitatory and inhibitory post-synaptic terminals, respectively [23]. Quantification of the two post-synaptic populations showed a marked increase in PSD-95 labeling (Figure 2B,C; p < 0.01) combined with a clear decrease of that of gephyrin (Figure 1E,F; p < 0.01), in scn1Lab AUG morphants, compared to controls (Figure 2A,D).…”
Section: Resultsmentioning
confidence: 99%
“…We focused on excitatory and inhibitory synapses by studying two important proteins that are markers of synaptic integrity, PSD-95 and gephyrin [23]. PSD-95, by its PDZ domains, serves as a scaffolding protein with a docking site for signaling proteins clustering around NMDA- and AMPA- type glutamate receptors, which are crucial for excitatory neurotransmission and synaptic plasticity [34].…”
Section: Discussionmentioning
confidence: 99%
“…Tissue blocks were then sectioned (30 µm) on a Leica cryostat, fixed in 4% formaldehyde (diluted from 16% paraformaldehyde Pierce Scientific) for 10 min and stained with synaptic antibodies as in ref. 38 . Anti-PSD-95 (1:500; Abcam; Cambridge, UK; ab-18258) and anti-Shank3ab (1:200; sc-30193, Santa Cruz Biotechnology, CA; this polyclonal has since been discontinued) were used as primary antibodies, with secondary antibodies conjugated to Alexa Fluor 568 (Abcam, ab175472) and Alexa Fluor 633 (Thermo Fisher Scientific, R21070), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…We recently showed that zebrafish gabra1 -/-and depdc5 -/-epileptic mutants displayed markedly fewer inhibitory synapses compared to age-matched control larvae, showing that these two mutants display brain development defects [21], [22]. To determine whether Scn1Lab deficiency also induced unbalanced excitatory/inhibitory post-synaptic outputs, we analyzed and compared, by immunocytochemistry, the distribution of the two post-synaptic populations on brain sections of 5 dpf control and Scn1Lab-depleted larvae, using anti-PSD-95 and anti-gephyrin antibodies, which label excitatory and inhibitory post-synaptic terminals, respectively [23]. Quantification of the two post-synaptic populations showed a marked increase in PSD-95 labeling (Figure 2B, C; p < 0.01) combined with a clear decrease of that of gephyrin ( Figure 1E, F; p < 0.01), in scn1Lab AUG morphants, compared to controls (Figure 2A, 2D).…”
Section: Inhibitory/excitatory Synaptic Balance Is Disrupted In Scn1lmentioning
confidence: 99%